ANALYSIS OF EFL LEARNERS’ COMPETENCE IN USING ANAPHORA REFERENCE IN READING TECHNICAL TEXT - Maspufah Maspufah (Universitas Lancang Kuning, 2018)
Reading is one of four basic skills which should be mastered by English majoring students. They are demanded to be able to gain information all kinds of texts well since their learning material and references were taken from English written book. In fact students had problem with motivation, limited vocabulary, and background knowledge. This research is a descriptive research. The purpose of the research was to find out the students’ competence in using reference in reading technical text. The subject of the research was thirteen students of fourth semester of 2017/2018 ABA Persada Bunda Pekanbaru. The instrument used to collect the data was reading test in the form of multiple choice tests. The result were analyzed to find out the level of students’ competence in using reference in technical text. From the finding, it was found that: (1) The students’ competence in using personal reference in thechnical text was in good category. They had problems with motivation and lack of background knowledge in mastering personal reference (2) the students’ competence in using demonstratives reference in narrative texts was in good category. The problems occurred because they had limited vocabulary and lack of motivation. Thus, it can be concluded that the students’ competence in using reference in technical text still needed to be improved because they still had limited vocabulary and lack of motivation.